PKM KWT SEKAR TRANSAD: SOLAR DOME DRYER UNTUK EFISIENSI PENGERINGAN DAN HIGIENITAS PRODUK PASCAPANEN - Deni Subara; Dyah Putri Larassati; Okta Amelia (Jurnal Abdi Insani, 2026)
This community service research aims to address the challenges of non-hygienic and weather-dependent traditional drying methods in processing agricultural waste among the Sekar Transad Women Farmers Group (KWT). The primary focus is to implement and test renewable energy-based drying technology to convert pineapple and banana peels into economically valuable flour, thereby meeting the demand for production efficiency and hygiene. The implementation method adopted a participatory, partnership-based approach, engaging KWT partners from the initial design and construction phases. A solar dome dryer unit with a capacity of 500 kg of wet raw material was constructed using polycarbonate material and a light steel frame. Following construction, intensive training was conducted, covering operational protocols, routine maintenance, and quality testing techniques, ensuring the community members achieved full technological mastery. The evaluation of the solar dryer's performance yielded highly satisfactory results. The solar dome drying unit successfully reduced the drying process duration significantly by up to 40% compared to conventional methods, effectively cutting the time from two full days to one. The enclosed design maintained stable internal temperatures above 55°C, a critical threshold for suppressing microbial contamination and pathogenic growth. Post-drying analysis confirmed that the waste flour produced had consistent moisture content, met industrial quality standards, and exhibited significantly superior hygiene levels. The successful adoption of this technology provides a crucial solution to weather fluctuations, guarantees production continuity, and substantially increases the market value of the processed waste products. Thus, the implementation of the solar dome drying system proves to be an innovative, sustainable, and measurable solution for zero-waste management at the community level. The adoption of this renewable energy technology holds significant implications for strengthening local food security and supporting the economic independence of small enterprises through process efficiency.